Pengaruh Penambahan Puree Kacang Merah (Phaseolus vulgaris) Terhadap Karakteristik Nugget Jamur Tiram (Pleurotus ostreatus) - Sinaga, Elsa Fanora; Suparthana, Putu; Hapsari A., Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i03.p14, 2021)
This study was aimed to determine the effect of adding red bean (Phaseolus vulgaris) puree to oyster mushroom nugget food and to see the correct amount of addition of red bean puree in producing oyster mushroom nuggets with the best criteria. The experimental design used in this research was a Completely Randomized Design (CRD) with an addition of red bean puree that consisted of 5 treatments namely: 0%; 10%; 20%; 30%; and 40%. The treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect then followed by Duncan’s Multiple Range Test (DMRT). The addition of red bean puree affected water content, ash content, protein content, crude fiber content, hedonic test (texture, aroma, taste and overall acceptance) and scoring test (texture). The addition of 40% red bean puree ratio of had the best characteristics with water content of 32,67%, ash content of 1,57%, protein content of 7,29%, crude fiber content of 6,47%, hedonic test (texture, taste and overall acceptance) was liked, aroma was disliked and scoring test of taste was chewy.